Electrical power systems design and analysis - El-Hawary, M. E. (IEEE Press power systems engineering series, 1995)
"This comprehensive textbook introduces electrical engineers to the most relevant concepts and techniques in electric power systems engineering today. With an emphasis on practical motivations for choosing the best design and analysis approaches, the author carefully integrates theory and application. Key features include more than 500 illustrations and diagrams, clearly developed procedures and application examples, important mathematical details, coverage of both alternating and direct current, an additional set of solved problems at the end of each chapter, and an historical overview of the development of electric power systems. This book will be useful to both power engineering students and professional power engineers."